Analisis Kemampuan Berfikir Kreatif Matematis Siswa SMK Pada Materi Sistem Persamaan Linier Dua Variabel (SPLDV) Di Kota Cimahi - Ai Rasnawati; Windi Rahmawati; Padillah Akbar; Harry Dwi Putra (Mathematics Education Study Program, 2019)
Mathematical creative thinking is the ability to think that aims to solve a problem with many ideas, produce ideas that are diverse, can create new ways and have no similarities with others and are able to develop an idea. Indicators of students' mathematical creative thinking abilities used are fluency, flexibility, originality and elaboration. This study aims to determine the mathematical creative thinking skills of vocational students in Cimahi City on the material of two-variable linear equation systems. This type of research is descriptive qualitative research. The instrument used is in the form of a test of creative thinking skills in the form of a description, a question given to students of class X as much as 31 students. Students in one of the Vocational Schools in Cimahi City. The results of the study show that the ability of students in creative thinking on the material system of linear variables is still low, only 39% of the students' answers reached the maximum score.